Web-Based Information System Design for Cempaka Putih Group Savings and Loans Unit: Rancang Bangun Sistem Informasi pada Unit Simpan Pinjam Cempaka Putih Group Berbasis Web - Asril; Remeta Saputri; Try Hadyanto (Journal of Vocational Education and Information Technology (JVEIT), 2026)
The Cempaka Putih Group Savings and Loan Unit currently manages customer records and loan applications using manual procedures, resulting in recording errors, inefficient data retrieval, delays in report generation, and reduced operational efficiency. These limitations highlight the need for an integrated information system to improve the effectiveness of administrative and financial management. This study aims to design and develop a web-based information system that supports customer data management, loan application processing, and report generation in an integrated platform. The system was developed using the Waterfall software development model, which consists of requirements analysis, system design, implementation, testing, and maintenance. System modeling was performed using the Unified Modeling Language (UML), while the application was implemented using PHP and MySQL. Functional evaluation was conducted through Black Box Testing to verify that the system met the specified functional requirements. The results demonstrate that the developed system successfully integrates member registration, customer data management, loan application processing, and reporting into a single web-based platform. Functional testing confirmed that all major system features operated correctly without functional errors. The implementation of the proposed system improves data management efficiency, accelerates information retrieval, minimizes recording errors, and supports more accurate and timely report generation.